Proses Collaborative Governance dalam Penanganan Banjir di Kota Semarang City - Hidayatullah, Muhammad Arif; Purnaweni, Hartuti; Yuwono, Teguh (Universitas Indo Global Mandiri, 2023)
This study discusses the process of collaborative governance in handling floods in the city of Semarang. The phenomenon is that the people's mindset is not in line with the disaster mitigation system, the increased risk of flood disasters due to the growth and expansion of settlements and industry, and the lack of optimal coordination in flood handling and rehabilitation. The research objective is to analyze the collaboration process that occurs in handling floods in the city of Semarang and the supporting and inhibiting factors. The research method used is a qualitative method. The results of research show that the collaboration process has been going well, which consists of face-to-face dialogue, trust building, commitment to process, shared understanding, and intermediate outcomes. However, the share understanding indicator is not optimal due to differences in understanding of the problems faced by the private sector and the community with BPBD Semarang City. Supporting factors are network structures that are well built with each other and there is no hierarchy in this network; commitment through the efforts each goes through; trust in one another; information that is easily accessed; and human resources involved. The inhibiting factors are governance, distributive accountability and responsibility, and access to resources. Obstacles encountered can come from the government itself, where there is minimal transparency, no division of decisions that can hinder collaboration, and technical implementation due to constraints on authority that are compartmentalized.